Achieving green environment targets in the world's top 10 emitter countries: the role of green innovations and renewable electricity production. Issue 1 (31st December 2022) - Jun, Wen; Mughal, Nafeesa; Kaur, Prabjot; Xing, Zhaopeng; Jain, Vipin; The Cong, Phan
Abstract: The rapid pace of industrialisation and economic development in recent decades is not without its environmental consequences. Electricity production, though an important determinant of economic development, remained under studied in the existing literature and only a few models on the electricity production-environmental degradation nexus are available. As a first attempt, this study examines the impact of renewable and non-renewable electricity generation and eco-innovations on CO2 emissions in the world's top emitting countries under the umbrella of the Environmental Kuznets Curve (E.K.C.) Hypothesis. Second-generation panel data techniques, i.e., C.I.P.S. and Bai and Carrion-I-Silvestre (2009 ) unit root tests, Westerlund and Edgerton (2008 ) and Banerjee and Carrion-i-Silvestre (2017 ) cointegration techniques and Cross-Sectionally Augmented Distributed Lag Model for short and long run coefficient estimations have been employed in the study. It is found that renewable electricity production and eco-innovations have negative effects, whereas non-renewable electricity production has positive effect on CO2 emission. Moreover, the estimation demonstrated the E.K.C. validation in these countries. It is recommended that fossil fuel dependency in the electricity sector should be reduced by devising policies directed towards green electricity measures. More investment in green innovations to achieve green environment and sustainable growth is also recommended by the study.